Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1149/1.2096955
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Studies of Crystalline CVD Silicon Nitride

Abstract: 15271. The diffusion model successfully predicted minimum A1 concentrations for protective A1203 scale formation during cyclic oxidation of Ni-Cr-AI(Zr) alloys containing more than 20% Cr.2. The success of the diffusion model in predicting N~ is strongly dependent on the ability to account for partial oxide spallation. The use of the oxide spalling model (16) provides this ability.3. It is not necessary to account for surface recession or the effect of the Cr concentration gradient on the diffusion of A1 when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(90 citation statements)
references
References 13 publications
2
88
0
Order By: Relevance
“…The evidence that supports a discrete oxynitride phase is the discontinuity in the etching rate of the oxide scale formed on silicon nitride (Du et al, 1989a) as well as the contrast observed in TEM and SEM images of scale cross-sections (Ogbuji and Smialek, 1991). An SEM image of the oxynitride/oxide formedon Si3N4 is shownin Figure8.…”
Section: Oxidation Of Pure Si3n4 In Dry Oxygenmentioning
confidence: 92%
See 1 more Smart Citation
“…The evidence that supports a discrete oxynitride phase is the discontinuity in the etching rate of the oxide scale formed on silicon nitride (Du et al, 1989a) as well as the contrast observed in TEM and SEM images of scale cross-sections (Ogbuji and Smialek, 1991). An SEM image of the oxynitride/oxide formedon Si3N4 is shownin Figure8.…”
Section: Oxidation Of Pure Si3n4 In Dry Oxygenmentioning
confidence: 92%
“…The oxidation of silicon nitride typically occurs with parabolic kinetics (Choi et al (1989), Du et al, 1989a;Schiroky et al (1986); Ogbuji and Opila, 1995), is dependent on oxygen partial pressure, and is independent of nitrogen partial pressure (Du et al, 1989a). These three observations show that the oxidation kinetics are controlled by oxygen transport across a growing scale.…”
Section: Oxidation Of Pure Si3n4 In Dry Oxygenmentioning
confidence: 97%
“…20,64,66,[102][103][104][105][106] This history dependence can perhaps be appreciated most easily through a survey of the silicon oxynitride (SiO x N y ) literature, or through the variability of experimental outcomes when proper care is not taken. 66,107,108 A surface oxide coating readily forms in air (and can lead to an oxide gradient into the film), 102,108,109 and the susceptibility of Si 3 N 4 to evolve ammonia by hydrolysis in the presence of liquid-and vapor-phase water should also be considered. 102,103 In spite of this, SiN x shows very strong chemical resistance to a wide range of etchants and conditions, and indeed, etch resistance is the mechanism by which the film is made freestanding.…”
Section: Thin-film Silicon Nitride Membranesmentioning
confidence: 99%
“…111 The surface can be generally conditioned using standard approaches such as exposure to a suitable oxidizing or reducing environment, or wet etching including hydrofluoric acid (and analogues) or piranha solution (and analogues). 20,47,64,102,106,108,[114][115][116][117][118][119][120][121][122][123] Specialized extensions of these methods can bring additional chemical flexibility. 20,64,104 Silane chemistry is a common route to surface chemical functionalization, but one that can be undermined by insufficient attention to either the SiN x process history or to the demands of the silane reaction itself.…”
Section: Thin-film Silicon Nitride Membranesmentioning
confidence: 99%
“…42 The third component at 100.91 eV is assigned to Si-Si within silicon core of NPs. [43][44] The C1s spectrum is fitted with three components and a Shirley background, see Fig. 2c.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%